Microfinance and Social Performance in Africa - Halouani, Nihel; Boujelbene, Younes (Indian Journal of Finance, 2011)
In this paper, MFI’s social performance is measured in terms of outreach: Depth of outreach and breadth of outreach, and quality of outreach or Assessment Impact using the % of Women Borrowers to measure this variable. The researchers used these variables to test the relationship between Social Performance and geographical diversification in African zones, and to examining the effect of regulation on MFIs social performance. The researchers looked for evidence that regulation provides economics benefits by improving loan quality. The researchers used data from 26 countries, 168 MFIs, over the period 2005-2008. The researchers developed an empirical model of SP. The main conclusion of this study is that Depth of outreach, the number of active borrowers and the percentage of women borrowers do not have the same results in different areas of Africa. The findings are consistent with the theories that hypothesize that the social, cultural, legal, regulatory and economic variations affect the SP of MFIs. Regulation is found to negatively affect the Depth of outreach and the percentage of Women Borrowers; it has a positive relationship with the number of active borrowers. In fact, it is evident that average loan and the number of borrowers substitute each other in terms of effects: Adding one borrower may reduce the value of the average loan. This result is not constant over the regions of Africa.